Public speaking with confidence (Victoria : Ash Quarry Productions, 1990)
Whether it is to give a speech at a conference, run a training session or give a media interview, most people experience anxiety when speaking in public. Experienced speakers and presenters have learned the secrets of developing confidence - now you can discover them too
Bibliographical information is taken from the publisher's catalogue
Keywords: Public speaking